MODEL INTEGRATIF BUDAYA KERJA BERKUALITAS, KETERLIBATAN KARYAWAN, DAN ADAPTASI DIGITAL TERHADAP KINERJA SUMBER DAYA MANUSIA UMKM DI SURABAYA - Fredy Apritama Djunaidi; Galang Febriansyah; Junaidi Efendi (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze and develop an integrative model that combines quality-based work culture, employee engagement, and digital adaptation in improving human resource (HR) performance within urban MSMEs in Surabaya. The background of this research is based on the common issue of relatively low HR performance in MSMEs, which is reflected in inconsistent work quality standards, limited employee participation in organizational processes, and suboptimal use of digital technology in daily operations. These conditions tend to reduce productivity and weaken the competitiveness of MSMEs in an increasingly dynamic business environment (Putri, 2020). This research adopts a qualitative approach using a literature review method, drawing from relevant national and international journals as well as academic books. The data were analyzed descriptively by integrating theoretical perspectives and findings from previous studies to construct a comprehensive conceptual framework. The findings indicate that a quality-based work culture plays a crucial role in establishing consistent work standards and encouraging continuous improvement (Gaspersz, 2017). Meanwhile, employee engagement significantly contributes to higher levels of motivation, commitment, and responsibility, which in turn positively affects both individual and organizational performance (Robbins & Judge, 2017). In addition, digital adaptation serves as a supporting factor that enhances work efficiency and streamlines business processes through the utilization of digital tools, such as online platforms, financial applications, and digital marketing channels (Zhao et al., 2022). The integration of these three variables creates a synergistic effect that improves productivity, output quality, and overall organizational effectiveness. In this context, employee engagement acts as a reinforcing factor that strengthens the implementation of quality-oriented work culture within a digitally driven environment (Rahman, 2021). The implication of this study suggests that MSMEs need to develop a more adaptive HR management approach that not only emphasizes work quality but also fosters employee involvement and digital capability. Therefore, the proposed integrative model can be considered as an alternative strategy to enhance HR performance sustainably and to strengthen the competitiveness of MSMEs in the era of digital transformation. This study aims to analyze and develop an integrative model that combines quality-based work culture, employee engagement, and digital adaptation in improving human resource (HR) performance within urban MSMEs in Surabaya. The background of this research is based on the common issue of relatively low HR performance in MSMEs, which is reflected in inconsistent work quality standards, limited employee participation in organizational processes, and suboptimal use of digital technology in daily operations. These conditions tend to reduce productivity and weaken the competitiveness of MSMEs in an increasingly dynamic business environment (Putri, 2020). This research adopts a qualitative approach using a literature review method, drawing from relevant national and international journals as well as academic books. The data were analyzed descriptively by integrating theoretical perspectives and findings from previous studies to construct a comprehensive conceptual framework. The findings indicate that a quality-based work culture plays a crucial role in establishing consistent work standards and encouraging continuous improvement (Gaspersz, 2017). Meanwhile, employee engagement significantly contributes to higher levels of motivation, commitment, and responsibility, which in turn positively affects both individual and organizational performance (Robbins & Judge, 2017). In addition, digital adaptation serves as a supporting factor that enhances work efficiency and streamlines business processes through the utilization of digital tools, such as online platforms, financial applications, and digital marketing channels (Zhao et al., 2022). The integration of these three variables creates a synergistic effect that improves productivity, output quality, and overall organizational effectiveness. In this context, employee engagement acts as a reinforcing factor that strengthens the implementation of quality-oriented work culture within a digitally driven environment (Rahman, 2021). The implication of this study suggests that MSMEs need to develop a more adaptive HR management approach that not only emphasizes work quality but also fosters employee involvement and digital capability. Therefore, the proposed integrative model can be considered as an alternative strategy to enhance HR performance sustainably and to strengthen the competitiveness of MSMEs in the era of digital transformation.